Kuasa Aktor dalam Perumusan Kebijakan Publik di Aras Lokal: Studi pada Kebijakan Pembebasan Lahan Kawasan Mandalika Resort di Lombok - Winengan, Winengan (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
This research is proposed an empirical phenomenon of local community opposition to the policy of land acquisition of Mandalika Resort Lombok Tengah area. This study aims to examine the involvement and power of the actors in the process of the birth of the policy. The design of this study using qualitative methods with the techniques of determining informants using snow ball. The results of this study revealed that the birth of the policy of land acquisition Mandalika Resort area is the result of political compromise between the Regional Government which relies on its power and PT. LTDC with its capital strength without the involvement of actors from local community elements. This research concludes that the close relationship between state and capital owners in policy formulation will be the reduction of public power as the actor of policy formulation, so the policy decision is less legitimacy